"‘A Peculiar Gift of Providence": The Power-Imbalance Caused by Gift-Giving in Millenium Hall - Snyder, Elisia (MacEwan University Student eJournal, 2015)
Sarah Scott’s eighteenth-century novel Millenium Hall canvasses the role of gift-giving in the dynamics heteronormative-domestic, economic, and spiritual relationships. The pharmakon of the gift plays a central role in Scott’s understanding of philanthropy, and the construction of her female-inhabited, female-run utopia. This article’s principle occupation is to show that all instances of gift-giving in Millenium Hall create power-imbalances between the superior giver and the inferior receiver; however, Sarah Scott’s female utopia constructs the most preferable type of subservience.